Analisis Pengelolaan Sampah Pasar Tradisional Berbasis Konsep Ekonomi Sirkular di Bank Sampah Sahabat Mitra - Sitorus, Adinda; Malau, Agnes; Aulia, Anisa; Zahira, Cut; sinurat, Ester; Syafii, Ridha; Kardiana, Elsa (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
Waste is a pressing global issue, especially in urban areas in Indonesia. Deli Serdang Regency faces serious challenges in waste management, especially from traditional markets that produce large amounts of organic and inorganic waste. This study aims to evaluate the implementation of a circular economy in market waste management through a case study of the Sahabat Mitra Waste Bank. The study was conducted through observation and interviews with waste bank administrators as well as market traders and visitors. The results showed that the Sahabat Mitra Waste Bank successfully managed an average of 1,200 kg of waste per month, producing products of economic value such as compost, liquid fertilizer, and maggot feed. Monthly income from waste management reached IDR 6,600,000, with an average customer income of IDR 62,857. This study shows that the circular economy approach has great potential in overcoming waste problems and creating sustainable economic and environmental benefits.